Effectiveness of neuromuscular electrical stimulation combined with rehabilitation training for treatment of post-stroke limb spasticity - He, Ya-long (Medicine (Baltimore), 2019)
BACKGROUND: This study aims to systematically explore the effectiveness of neuromuscular electrical stimulation (NMES) combined with rehabilitation training (RT) for the treatment of post-stroke limb spasticity (PSLS). METHODS: We will search Cochrane Library, MEDILINE, EMBASE, CINAHL, AMED, PsycINFO, WOS, Scopus, OpenGrey, and 4 Chinese databases from inception to the present without language restrictions. We will only consider randomized controlled trial on assessing the effectiveness and safety of NMES combined with RT for the treatment of PSLS. All included randomized controlled trials will be assessed using Cochrane risk of bias tool. Two researchers will independently perform study selection, risk of bias assessment, and data extraction, respectively. Any disagreements will be solved by a third researcher through discussion. RESULTS: Primary outcome is limb spasticity status. Secondary outcomes comprise of limb function, quality of life, and adverse events. CONCLUSION: This study will summarize the latest evidence of NMES combined with RT for the treatment of patients with PSLS. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42019138900.